In vivo Deep-Tissue Microscopy with UCNP/Janus-Dendrimers as Imaging Probes: Resolution at Depth and Feasibility of Ratiometric Sensing - Plunkett, Shane (Nanoscale, 2020)
Lanthanide-based upconverting nanoparticles (UCNPs) are known for their remarkable ability to convert near-infrared energy into higher energy light, offering an attractive platform for construction of biological imaging probes. Here we focus on in vivo high-resolution microscopy - an application for which the opportunity to carry out excitation at low photon fluxes in non-linear regime makes UCNPs stand out among all multiphoton probes. To create biocompatible nanoparticles we employed Janus-type dendrimers as surface ligands, featuring multiple carboxylates on one ‘face’ of the molecule, polyethylene glycol (PEG) residues on another and Eriochrome Cyanine R dye as the core. The UCNP/Janus-dendrimers showed outstanding performance as vascular markers, allowing for depth-resolved mapping of individual capillaries in the mouse brain down to a remarkable depth of ~1000 μm under continuous wave (CW) excitation with powers not exceeding 20 mW. Using a posteriori deconvolution, high-resolution images could be obtained even at high scanning speeds in spite of the blurring caused by the long luminescence times of the lanthanide ions. Secondly, the new UCNP/dendrimers allowed us to evaluate the feasibility of quantitative analyte imaging in vivo using a popular ratiometric UCNP-to-ligand excitation energy transfer (EET) scheme. Our results show that the ratio of UCNP emission bands, which for quantitative sensing should respond selectively to the analyte of interest, is also strongly affected by optical heterogeneities of the medium. On the other hand, the luminescence decay times of UCNPs, which are independent of the medium properties, are modulated via EET only insignificantly. As such, quantitative analyte sensing in biological tissues with UCNP-based probes still remains a challenge.